Adverse events following immunization of COVID-19 vaccine among children aged 6–11 years - Puspitarani, Fitriana (Frontier, 2022)
Introduction: Starting in December 2021, the Indonesian Government has recommended inactivated SARS-CoV-2 vaccine (CoronaVac) for children aged 6–11 years. This study aims to determine the prevalence and determinant factors of adverse events following immunization (AEFI) of the first dose and the second dose of the COVID-19 vaccine among children aged 6–11 years old. Materials and methods: We conducted a cross-sectional study in Bantul District, Yogyakarta, Indonesia, in February–March 2022. Data were collected by trained interviews with 1,093 parents of children 6–11 years old who received the first dose and the second dose of the COVID-19 vaccine. Data were analyzed with chi-square and logistic regression. Results: The prevalence of AEFI in the first dose of the COVID-19 vaccine was 16.7%, while the second dose was 22.6%. The most common symptoms of AEFI at the first dose were local site pain and fever, while at the second dose were cough and cold. Determinants of AEFI of COVID-19 vaccination among children were girls with OR 1.31 (95% CI 1.0–1.7; P 0.04), mass-setting of vaccination with OR 0.70 (95% CI 0.5–0.9; P 0.01), the history of AEFI in childhood vaccination with OR 1.63 (95% CI 1.2–2.2; P < 0.01) and administering other vaccines within 1 month before COVID-19 vaccination, with OR 5.10 (95% CI 2.1–12.3 P < 0.01). Conclusion: The prevalence of AEFI in the first and the second dose of inactivated COVID-19 vaccine was comparable to that reported in the clinical trial study and the communities. Risk communication should be provided to the child and their parents regarding the risk of mild AEFI of the COVID-19 vaccine, especially for children with a history of AEFI in childhood vaccination and who received other vaccines containing the same adjuvant with CoronaVac within 1 month. A mass-setting of vaccination should be taken as an advantage to educate parents about the risk of AEFI and also about the reporting pathways.